MEDIATIZED SPORT (Fiep Bulletin - online, 2013)
This theoretical essay represents an outline of sport as a mediatized social phenomenon, being able to articulate various social argumentative spheres. The sports show, in which we point out in particularly the Olympic Games and the World Cup, is also produced in advance by media, which through their pre-coverage set an agenda for the audience. This coverage doesn't always have in its contents elements which are restricted to the sports field. Media are responsible for the transcendence of senses and meanings from the sports field. The appeal to cultural, identity-forming aspects is the most recurrent in precoverage (we refer to aspects which transcend the field). In that sense, we understand that since the field of media is a symbolic actions producer, it has great importance in the social context.
Keywords: sports; mediatized; agenda